MODEL KOMUNIKASI ANTARBUDAYA MAHASISWA MUSLIM THAILAND DALAM PROSES AKULTURASI BUDAYA DI KABUPATEN JEMBER - Clara Sinta Pratiwi (Indonesian Journal of Islamic Communication, 2020)
Thai Muslim students are spread across various universities in Jember. In interacting as a minority community, Thai Muslim students have made various adaptations to the dominant culture of Jember which is known as phandalungan culture. It is caused by the majority of people in Jember are inhabited by people with Madurese and Javanese cultural backgrounds. The intercultural communication process of Thai Muslim students in the process of acculturation in Jember can be seen by the intercultural communication model by William B. Gudykunts and Alo Liliweri's tori of cultural acculturation. Qualitative methods with phenomenological studies reveal that the communication model of Thai Muslim students in the process of cultural acculturation in Jember by adapting seven elements of universal culture. In addition, the students have acculturation and produce various models of acculturation, namely assimilation, integration, marginalization, and separation. Communication of Thai Muslim students in dealing with the dominant culture in Jember Regency by first experiencing a process of cultural shock. The process of cultural shock is a process where students experience a new cultural clash that is different from their original culture.